Photo-Induced α-Oxyalkylation of Aryl Chlorides with Ethers and Alcohols through Homolytic Aromatic Substitution - Aoki, Kohei; Yonekura, Kyohei; Ejima, Wataru; Tanaka, Shota; Shigeta, Ami; Shirakawa, Eiji (Synthesis, 2024)
The α-oxyalkylation of aryl chlorides with ethers and alcohols using a small amount of a peroxide was found to be induced by photoirradiation. The reaction proceeds through a homolytic aromatic substitution (HAS) mechanism consisting of addition of an α-oxyalkyl radical to an aryl chloride and elimination of the chlorine atom to give the α-oxyalkylation product, where photoirradiation is considered to effect not only the initiation step to facilitate homolysis of a peroxide, but also the propagating radical chain.
Keywords: aromatic substitution; photoirradiation; radical reactions; reaction mechanism; synthetic methods